2016
DOI: 10.4049/jimmunol.1502527
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Human Cytomegalovirus Immediate Early Proteins IE1 and IE2 in the Transcriptional Regulation of MICA and PVR/CD155 Expression

Abstract: Elimination of virus-infected cells by cytotoxic lymphocytes is triggered by activating receptors, among which NKG2D and DNAM-1/CD226 play an important role. Their ligands, that is, MHC class I–related chain (MIC) A/B and UL16-binding proteins (ULBP)1–6 (NKG2D ligand), Nectin-2/CD112, and poliovirus receptor (PVR)/CD155 (DNAM-1 ligand), are often induced on virus-infected cells, although some viruses, including human CMV (HCMV), can block their expression. In this study, we report that infection of different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 81 publications
3
19
0
Order By: Relevance
“…Cells and viruses. Primary HFFs (ATCC strain SCRC-1041) and human embryonic kidney 293 (HEK 293) cells (Microbix Biosystems Inc.) were cultured in Dulbecco's modified Eagle's medium (DMEM) (Sigma-Aldrich) supplemented with 10% fetal calf serum (FCS) (Sigma-Aldrich) as previously described (39,64). The HCMVs used in this study were all bacterial artificial chromosome (BAC) clones.…”
Section: Methodsmentioning
confidence: 99%
“…Cells and viruses. Primary HFFs (ATCC strain SCRC-1041) and human embryonic kidney 293 (HEK 293) cells (Microbix Biosystems Inc.) were cultured in Dulbecco's modified Eagle's medium (DMEM) (Sigma-Aldrich) supplemented with 10% fetal calf serum (FCS) (Sigma-Aldrich) as previously described (39,64). The HCMVs used in this study were all bacterial artificial chromosome (BAC) clones.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, DDR-mediated pathway may be activated upon infection by several viruses, including herpes viruses, adenoviruses and retroviruses, and is responsible for NKG2DL up-regulation. However, while a direct link between these two phenomena has been established for HIV-1 [ 25 , 26 ], up-regulation of MICA upon human cytomegalovirus (HCMV) infection appears to be independent from DDR induction and is directly promoted by viral proteins [ 27 ]. In cancer cells, genotoxic stress increases the sensitivity of tumor cells to NK cell-mediated lysis by the induction of NKG2DL expression mainly through DDR activation [ 19 , 20 , 21 ].…”
Section: Nkg2d/nkg2d Ligand Axis In the Recognition Of Damaged Celmentioning
confidence: 99%
“…Additionally, we have previously shown that IE1 and IE2 expressed in this model cooperate to activate expression of different target genes (46). IE1 and IE2 proteins are known to have distinct functions (52), but at this point the mechanistic basis for the inhibitory effect of IE2 on P2Y2 expression outside the context of infection is unclear. IE1 protein expression alone induces P2Y2 RNA levels by a factor of about 16 ( Fig.…”
Section: P2y2 and P2x5 Exhibit Different Expression Kinetics During Imentioning
confidence: 86%